2005
DOI: 10.1074/jbc.m413969200
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Receptor-related Protein (LRP) Interacts with Presenilin 1 and Is a Competitive Substrate of the Amyloid Precursor Protein (APP) for γ-Secretase

Abstract: Presenilin 1 (PS1) is a critical component of the ␥-secretase complex, which is involved in the cleavage of several substrates including the amyloid precursor protein (APP) and the Notch receptor. Recently, the low density receptor-related protein (LRP) has been shown to be cleaved by a ␥-secretase-like activity. We postulated that LRP may interact with PS1 and tested its role as a competitive substrate for ␥-secretase. In this report we show that LRP colocalizes and interacts with endogenous PS1 using coimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 57 publications
(83 reference statements)
2
39
0
Order By: Relevance
“…Finally we could show here that SorLA is, like the amyloidogenic protein APP, a substrate for the presenilin-containing ␥-secretase complex, which is necessary for the production of the A ␤ -peptide. Therefore, SorLA might be a competitive substrate of APP for ␥-secretase similar to notch (55) and LRP (49). This could explain why reduced SorLA levels in brain would lead to an increased production of A ␤ and finally to the development of Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%
“…Finally we could show here that SorLA is, like the amyloidogenic protein APP, a substrate for the presenilin-containing ␥-secretase complex, which is necessary for the production of the A ␤ -peptide. Therefore, SorLA might be a competitive substrate of APP for ␥-secretase similar to notch (55) and LRP (49). This could explain why reduced SorLA levels in brain would lead to an increased production of A ␤ and finally to the development of Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%
“…CRB2 Is Not a Competitive Substrate for ␥-Secretase-It is still controversial whether ␥-secretase substrates competitively inhibit each others cleavage (25)(26)(27). CRB2 is a potential substrate for ␥-secretase, because CRB2 is a type I TM protein.…”
Section: Efficient Inhibition By Crb2 Requires Its Cytoplasmic Domainmentioning
confidence: 99%
“…79 In other studies, Ab1À40 has been found to reduce cholesterol synthesis by inhibiting the enzyme 3-hydroxy-3 methylglutaryl coenzyme A (HMG-CoA) reductase (involved in cholesterol synthesis), in a putative negative feedback loop, and Ab1À42 has been found to activate neutral sphingomyelinase, an enzyme that cleaves sphingomyelins to produce ceramides, thought to be primary effectors of apoptosis. 80 This latter finding is consistent with the fact that ceramide:sphingomyelin ratios are higher in vulnerable brain regions of AD patients.…”
mentioning
confidence: 99%